Modelling A-pillar overflow - Using a smoothed particle hydrodynamics based method - Larsson, Martin (My University, 2023)
A-pillar overflow is the event when fluid is transported from the windshield across the A-pillar, ending up on the driver side window, obscuring the driver’s vision. Simulations of A-pillar overflow can make initial predictions of how the driver’s vision will be affected during windscreen washing or rain, and reduce developmental costs by making earlier design changes. Earlier numerical simulations have been carried out using traditional Finite Volume Method (FVM) Computational Fluid Dynamics-solvers (CFD) based on hybrid methods using Lagrangian Particle Tracking (LPT) and Volume of Fluid (VOF). Since A-pillar overflow is a transient event with moving wipers, requiring a transient mesh, it increases the computational cost and can induce numerical instabilities. By applying a Smoothed Particle Hydrodynamics (SPH) solver the need for a mesh is removed, but this approach has less validated solvers and problems with particle size-dependent model constants. This thesis aims at investigating A-pillar overflow using an SPH-based solver, PreonLab, and qualitatively validate the simulation with physical tests. The purpose of the thesis is firstly to establish a feasible workflow to simulate a windscreen washing event. The wiper kinematics modelled by a multibody dynamics software, ADAMS, and the airflow computed by an FVM method in Star-CCM+ are imported to PreonLab. Model constants such as particle spacing, adhesion and roughness factor are studied using validation against simple physical test cases. Secondly, it is to simulate A-pillar overflow on the Volvo V90 and XC40, where the amount of liquid arriving on the driver side window is substantially different due to different styling around the A-pillar area. Results indicate that wiper cycle simulations could be conducted in PreonLab in the future, as the overall behaviour of the fluid is captured through tuning of model parameters. Due to a lack of validation of the surface parameters and the density used in the airflow implementation, the simulation method is not fully validated. Further studies on airflow-liquid interaction models and surface properties need to be done in order to capture the complicated physics of an A-pillar overflow simulation
Keywords: Wipers, Smoothed-Particle Hydrodynamics, IISPH, A-pillar overflow, Computational Fluid Dynamics, Surface wetting, Pairwise Force model.